2017
DOI: 10.7150/jbji.20404
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cavitary Bone Defects in Chronic Osteomyelitis: Bioactive glass S53P4 vs. Calcium Sulphate Antibiotic Beads

Abstract: Aim: To evaluate the efficacy of bioglass (BAG-S53P4) in the treatment of patients with chronic osteomyelitis and compare the results with calcium sulphate antibiotic beads in one medical centre.Methods: Retrospective analysis of 25 cases. Inclusion criteria: patients diagnosed clinically and radiographically of osteomyelitis and treated surgically (Group 1: cavitary bone defects treated with bioglass and Group 2: cavitary bone defects treated with calcium sulphate antibiotic beads) during the period of 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…In our experiment, PMMA and BAG granules started reducing the bacterial growth only after 24 h, while killing a large number of bacteria took at least 48–72 h after inoculation. In contrast, different studies reported a significant earlier drop (24 to 48 h) in the number of colony forming units when compared the activity of BAG S53P4 with PMMA or calcium sulphate antibiotic beads [ 17 , 18 , 20 ]. This may be explained by the use of test tubes containing the BAG mixtures in this experiment, which reduces the contact surface area between the agent and the culture medium, a factor that may have influenced the release of alkaline ions into the mixture, retarding its effect on bacterial inhibition [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiment, PMMA and BAG granules started reducing the bacterial growth only after 24 h, while killing a large number of bacteria took at least 48–72 h after inoculation. In contrast, different studies reported a significant earlier drop (24 to 48 h) in the number of colony forming units when compared the activity of BAG S53P4 with PMMA or calcium sulphate antibiotic beads [ 17 , 18 , 20 ]. This may be explained by the use of test tubes containing the BAG mixtures in this experiment, which reduces the contact surface area between the agent and the culture medium, a factor that may have influenced the release of alkaline ions into the mixture, retarding its effect on bacterial inhibition [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] 2014 76 C / a Munukka E. [ 21 ] 2007 29 a Ferrando A. [ 18 ] 2017 25 C / a Drago L. [ 22 ] 2013 27 20 M / a Leppäranta O. [ 23 ] 2007 15 a Lindfors N.C. [ 24 ] 2010 11 C / a Gergely I.…”
Section: Discussionmentioning
confidence: 99%
“…They compared the efficacy of bioglass (BAG-S53P4) and calcium sulfate antibiotic beads in the treatment of chronic osteomyelitis. For 13 patients (7 on tibia) with antibiotic-loaded calcium sulfate implantation, 12 patients achieved infection remission during the follow-up [20].…”
Section: Discussionmentioning
confidence: 99%
“…In another comparative study, Albert Ferrando et al compared the efficacy of bioglass (BAG-S53P4) and calcium sulphate antibiotic beads in the treatment of chronic osteomyelitis. For 13 patients (7 on tibia) with antibiotic-loaded calcium sulfate implantation, 12 patients achieved infection remission during the follow-up [22]. However, although the samples of their study were relatively large, it contained a variety of infection sites (femur, tibia, humerus, radius, ulnar, pelvic and even calcaneus) and four types of Cierny-Mader classification.…”
Section: Discussionmentioning
confidence: 99%